222k views
4 votes
Which is a reasonable first step that can be used to solve the equation 4 x + 3 (x + 2) = 5 (2 x minus 3)?

User Gaza
by
5.6k points

2 Answers

1 vote

Answer:

Distribute the 3 to x + 2, and distribute the 5 to (2x – 3)

Explanation:

User Ben Paton
by
5.4k points
3 votes

Answer:

The 3 steps you can use are as highlighted below, and the value of x is 7

Explanation:

4x + 3(x + 2) = 5(2x - 3)

Step 1: We expand first by opening the brackets

4x + 3*x + 3*2 = 5*2x -5*3

4x + 3x + 6 = 10x - 15

Step 2: we collect like terms on either side

4x +3x - 10x = -15 - 6

-3x = -21

Step 3: Divide both sides by -3

x = -21/-3

x = 7

User Marcostvz
by
5.2k points